2014
DOI: 10.15296/ijwhr.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Letrozole on Endometrial Histology in Patients with Disordered Proliferative Endometrium and Simple Hyperplasia

Abstract: Objectives: This is a preliminary study investigating the efficacy of aromatase inhibitor letrozol on endometrial histology in patients with disordered proliferative endometrium or simple hyperplasia. Materials and Methods: In a randomized clinical trial, 92 patients with abnormal uterine bleeding who had disordered proliferative endometrium or simple hyperplasia in endometrial biopsy, were randomized into case and control groups. patients received 2.5 mg of letrozole daily in case group (n=46) and 40 mg of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A recent study in Iran showed that pre and postmenopausal women with disordered proliferative endometrium or simple hyperplasia can be successfully treated with letrozole alone 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in Iran showed that pre and postmenopausal women with disordered proliferative endometrium or simple hyperplasia can be successfully treated with letrozole alone 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In 63% of patients endometrium was atrophic and the ultrasound endometrial thickness was 5 mm or less. In 31% of patients, the endometrial histology was abnormal and ultrasound endometrium was greater than 5mm and they suggested that an endometrial thickness of 5 mm is an appropriate cutoff level for conservative management of patients with postmenopausal bleeding 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs involving 142 patients reported regression rates for LET (94.4%, 67/71) and MA (88.7%, 63/71) [31,34]. The rates did not differ significantly between the two groups (RR 1.04, 95% CI 0.95-1.14, p = 0.423; I 2 = 8.2%; Figure 5D).…”
Section: Let Vs Mamentioning
confidence: 95%
“…The rates did not differ significantly between the two groups (RR 1.04, 95% CI 0.95-1.14, p = 0.423; I 2 = 8.2%; Figure 5D). [32,35,39,41], (C) a comparison of MA and MA + MET [43,47], or (D) a comparison of LET and MA [31,34].…”
Section: Let Vs Mamentioning
confidence: 99%
See 1 more Smart Citation